Effect of nanoparticles additives on tribological behaviour of advanced biofuels. (15th February 2023) - Loo, Dong Lin; Teoh, Yew Heng; How, Heoy Geok; Le, Thanh Danh; Nguyen, Huu Tho; Rashid, Tazien; Pottmaier, Daphiny; Sher, Farooq
Graphical abstract: Highlights: Tribological performance of MgO, graphene and Al2 O3 nanoparticles blend in FTPO-biodiesel-diesel fuel were evaluated. 0.1 wt% concentration of all type nanoparticles additive provides the better performance on anti-friction in the blended fuel. Al2 O3 nano-fuel showed the best anti friction and wear performance. MgO nano-fuel showing the better surface performance and consistency. MgO nanoparticles had better overall tribological performance among all type of nanoparticles investigated. Abstract: The energy crisis and climate change have brought attention to developing alternative fuels. Waste tire pyrolysis oil is one of the most effective and renewable alternative fuels. Still, the TPO fuel had poor anti-wear properties than either biodiesel or diesel fuel, resulting in the studies conducted with nanoparticles. The lubricity of fuel is one of the important properties since it is the only lubricant in an engine injection system. Nanoparticles can be used as fuel additives to enhance better lubrication performance. This study presents the tribological behaviour of filtered tire pyrolysis oil (FTPO)-biodiesel-diesel blended fuel with the addition of various types of nanoparticles, including magnesium oxide (MgO), graphene (G), aluminium oxide (Al2 O3 ). The tribological experiments were conducted with Four ball tribo-tester, according to the ASTM-D4172 standard at 40 kg, 1200 RPM constant speed and 75 °C temperature. Low concentration for all types of nanoparticle additives provides better performance on anti-friction in the blended fuel due to the protective film formed between the contact surface. 0.1 wt% of Al2 O3 nano-fuel showed the best anti-wear performance, which improved by 2.83% compared to the base fuel Al2 O3 -0.1 and Al2 O3 -0.2, both reduced 22.09% and 18.33% of WSD, respectively, in compared to PB20FTPO10. The study results indicate that the addition of 0.2 wt% MgO nanoparticles performs well in obtaining smooth surface roughness. The Scanning Electron Microscope and Alicona images show lesser wear and damage to the surface with 0.1 wt% concentration of nano-fuel.